Optimalisasi Sayuran Buncis Sebagai Upaya Peningkatan Perekonomian Keluarga di Desa Meunasah Kulam - Sari Wardani; Rahmawati Cut; Rina Mirdayanti; Meliyani Safitri Dewi (Universitas Lancang Kuning, 2021)
Meunasah Kulam Village is located in North Aceh Regency of Aceh Province with the main income of the people sourced from the agricultural sector, namely farming and raising. In the mass Covid-19 pandemic, people are required to carry out activities at home in order to break the chain of spread of Covid-19 as a result of the decrease in income in the community. The solution offered through community service activities is to carry out mentoring of home business activities so as to increase family production. Home business produced crispy beans products. The activity was held in Geucik house which was attended by housewives. The activity stage consists of the preparation stage, the product processing stage and the product marketing stage. The conclusion of this community service activity is that mothers become more skilled in processing foodstuffs, especially green beans vegetables into more interesting products and preferably the community especially children so as to improve the family economy, especially during the covid-19 pandemic